Water Quality and Wastewater Treatment Methods from the Process of Dyeing Cloth with Indigo Dye in Northeastern Thailand - Suwanpakdee, Supannee; Senasri, Naiyana; Chumnanka, Nattiya; Simawan, Jitra; Phlaetita, Wasana; Pimolrat, Pornpimol; Sriyasak, Patcharawalai (Trends in Sciences, 2024)
The process of producing indigo dyed cloth involves a step of washing the dyed cloth, which requires a large amount of water and generates wastewater that cannot be reused and may have negative impacts on the environment. This research study collected 31 samples of wastewater from the process of dyeing cloth with indigo dye from production sources in Sakon Nakhon, Nakhon Phanom, and Mukdahan provinces to analyze the water quality and study wastewater treatment methods at laboratory scale using filtration and chemical methods, which employed aluminum sulfate, lime, and chlorine as coagulants. From the study, it was found that the collected samples of wastewater from the process of dyeing cloth with indigo dye had water quality that exceeded the standards set by the Department of Pollution Control. The average color value was 1,040.86 ± 744.83 PCU, the average COD was 711.59 ± 695.07 mg/L, the average total suspended solid was 1,495.87 ± 1,583.17 mg/L, and the average of total settable solids was 20.52 ± 25.85 mg/L. Therefore, the wastewater should be treated before being discharged into the public water system. Regarding the treatment of wastewater from the dyeing process, it was found that the most effective method is chemical treatment using lime and chlorine, which can reduce color in the wastewater by 98.73 %, COD by 91.67 %, total suspended solids by 97.09 %, and total settable solids by 96.47 %. The 2nd-best method is the use of aluminum sulfate, followed by filtration. All in all, both methods of treating the dyed fabric wastewater can improve the water quality to meet the standard before being used for beneficial purposes or discharged into public water sources, and the appropriate method of treatment can be selected for each area to minimize environmental impact. HIGHLIGHTS The analysis of the wastewater from indigo dyeing processes revealed that color, COD, total suspended solids, and total settable solids exceeded the wastewater standard The methods of treating the wastewater by chemical treatment using lime and chlorine, and aluminum sulfate can improve the water quality to meet the pollution standard The most effective method is chemical treatment using lime and chlorine This research provides a sustainable way to produce environmentally friendly natural-dyed fabrics GRAPHICAL ABSTRACT